Implementation of the Numbered Head Together (NHT) Learning Model to Improve Student Chemistry Learning Outcomes in Vocational Schools - Noli Krisnanto; Hartono Hartono; Rahman Susanto (Pedagogy Review, 2023)
Abstract: Implementation of Numbered Head Together (NHT) learning model to improve the student learning result in senior high school (SHS). This research aimed to determine the implementation of Numbered Head Together (NHT) learning model to improve the student learning result in senior high school (SHS) in studying chemistry. This research is conducted in SMKN 4 Palembang which the subject of research is students in X class. The populations are class X TKJ 3, the subjects were 36 students. The research is conducted by teaching students with Numbered Head Together (NHT) learning model. This research was conducted in two cycles, each cycle consisting of two meetings. The data were obtained by using observation sheet and test instrument of student learning result which was done at the end of the meeting. Improvement of student learning outcomes can be seen from the average of student learning outcomes before the action done (T0) of 70,00 with mastery learning 58,33%, an increase in cycle I (T1) to 77,22 with mastery learning 77,78% and in cycle II (T2) increased to 83,06 with learning mastery 86,11%.Keywords: classroom action research, numbered head together (nht) learning model, student chemistry learning result